I Cultural Identity in the Digital Era: cultural identity in the digital era - Riski Dwi Putri; Eko Purwanto; Nazla Keyla; Rapih N. Kharismatika; Kholifia A. Muthmainah (FISIP UPNVJ, 2024)
In the ever-evolving digital era, significant transformations are taking place in cultural identity. The digital environment has developed a more malleable and unrestricted setting, allowing individuals to express themselves freely. The relationship between culture and digital technology has changed the dynamics of cultural engagement, creativity, and the dissemination of cultural objects. However, these changes also introduce new obstacles, such as intercultural conflict and dehumanization, which can affect emotions and personal identity. In the realm of digitalization, the formation of cultural identity is influenced by factors such as liberal virtual spaces, the use of communication technologies for storytelling purposes, and communicative transformations and connections. Digital technology also facilitates the process of cultural assimilation between diverse cultures by promoting cross-cultural interactions through digital platforms. Digital media such as films, music and games play an important role in shaping cultural identity, while the maintenance of cultural identity in online communities is ensured through complex interactions between various elements. Many challenges arise in maintaining cultural identity in the digital era, including concerns regarding digital identity security and identity management in an ever-evolving environment. However, digital technology also offers opportunities to improve understanding of cultural identity through digital education and the protection of cultural heritage. In general, the digitalization process has influenced how individuals perceive, communicate, and respect their cultural identity. Although introducing new challenges, digital technologies simultaneously offer the possibility of strengthening and expanding cultural identities in an increasingly interconnected global society.